Chiari Malformation Type 1 And Syringomyelia Together with a Colloid Cyst and Hydrocephalus - Abdul Jaleel, Aishath Zeena; Niyaf, Ali; Bhattarai, Robin; Niraula, Kiran (Eastern Green Neurosurgery, 2026)
Background: Chiari malformation (type 1) is a rare condition in which the cerebellar tonsils descend through the foramen magnum into the spinal canal. This in turn leads to compression of the spinal cord at foramen magnum interfering with the flow of cerebrospinal fluid leading to craniospinal dissociation and as a result hydrocephalus and syringomyelia. Sometimes it occurs secondary to space occupying lesions in intracranial compartments.